Proceedings of the 50th Hawaii International Conference on System Sciences (2017) 2017
DOI: 10.24251/hicss.2017.278
|View full text |Cite
|
Sign up to set email alerts
|

Preservation of Indigenous Culture among Indigenous Migrants through Social Media: The Igorot Peoples

Abstract: The

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…The same procession also occurs in other Malay regions, precisely in the Philippines. The results of Botangen et al (2018), research conducted in the region show that the Igorot Community performs traditional ceremonies and rituals related to the beliefs of each tribe in the Cordillera. They give sesaji by providing animals, such as chickens, pigs, and cows.…”
Section: Supernatural Powermentioning
confidence: 99%
See 1 more Smart Citation
“…The same procession also occurs in other Malay regions, precisely in the Philippines. The results of Botangen et al (2018), research conducted in the region show that the Igorot Community performs traditional ceremonies and rituals related to the beliefs of each tribe in the Cordillera. They give sesaji by providing animals, such as chickens, pigs, and cows.…”
Section: Supernatural Powermentioning
confidence: 99%
“…The meaning of mutual cooperation owned by Betawi is similar to the value attached to the Binnadang culture of the Igorot community in the Philippines. Botangen et al (2018), this culture is a traditional practice of helping especially those in need by volunteering in community-related work. Another assistance that can be provided is financial and material support.…”
Section: Martial Arts and Oral Traditionsmentioning
confidence: 99%
“…When someone in the community is in need, especially in difficult times (for example, sickness, death in a family, or in times of disasters), the community comes to the aid of whoever is in need. Similar to alluyon, Botangen, Vodanovich andYu (2017, p. 2306) As Igorots became participants in mainstream development initiatives, their practice of working together as a community found its application in current community development projects. Adelina, one of the elder participants, shared that despite subsistence living, their community still practice alluyon not only in farming, building a neighbour's house, preparing and serving food, and doing work together during rituals, but also in community projects, such as the construction of a community hall, building and repair of schools, manual road works and road repairs after typhoons, clearing of communal pathways, and in organising POs (A. Pater, personal interview, 2 January 2009).…”
Section: Incorporating the Traditional Practice Of Working Together Imentioning
confidence: 99%
“…The concept of translocal and transnational modes of cultural reproduction proposes a dynamic and continually evolving view and experience of the global world through transgression of boundaries between spaces of very different scale and type, as well as through the re-creation of local distinctions between those spaces (Freitag & Oppen, 2010, p. 6). It has been observed that migration has given Indigenous Peoples access to global exploration and connection, resulting in redefining their Indigenous image and identity through technology and social media (Botangen et al, 2017;Longboan, 2009). As Igorots continue to move and interact in different parts of the world, studies show that they work towards making meaning of their culture of origin in the new space they are in.…”
Section: Potential and Challenges Of The Ili Concept Of Organisingmentioning
confidence: 99%
“…Scholars have touched on issues such as the use of ICT for intra-community communication or outreach communication purposes (Aarsaeher, Riabova, & Baerenholdt, 2004;Csonka & Schweitzer, 2004;Landzelius, 2006), the fostering of pan-indigenous identities (Niezen, 2009), or the use of ICTs to make political claims (Petray, 2011). Other research has indicated the use of ICTs to increase cultural resilience from traumatic historical events (Molyneaux et al, 2012), or to promote cultural revitalization (Botangen, Vodanovich, & Yu, 2017;McMahon, 2013). Marisa Duarte (2017), for instance, recognizes that "while SNS (social networking sites) are far from being egalitarian participatory democratic spaces for Indigenous peoples, they offer a compelling set of communicative affordances" (p. 1).…”
Section: Introductionmentioning
confidence: 99%